New Advances and Directions in Testicular Cancer - Garnick, Marc B (Revista Brasileira de Cancerologia, 2023)
Major advances have taken place in the overall management of patients with ali forms of testicular cancer The current articie reviews the approach to diagnosis, staging, and treatment of patients with both seminomatous and nonseminomatous germ celi cancerof the testis. The use of radiation therapy for patients with seminoma, as weli as new treatment modalities for patients with advanced forms of germ cell cancer of the testis, are outlined in full. Future directions are discussed, with an emphasis on new chemotherapeutic modalities in the overall management of the disease.